The effects of circuit strength training on the development of physical fitness and performance-related variables in handball players - Hermassi, S.; Laudner, K.; Schwesig, R. (Journal of Human Kinetics, 2020)
The purpose of this study was to determine the effects of 12 weeks of circuit training on physical fitness in handball players. Subjects were randomly divided into a circuit strength training group (CT, n = 10) and a control group (CG, n = 9). Training sessions and matches were performed together, but during the 12-week intervention, the experimental group replaced part of the regular regimen with circuit strength training. Measures assessed in both groups before and after the intervention included: the agility T-half Test, the Yo-Yo intermittent recovery test, squat and counter-movement jumps, 15 m and 30 m sprints, and strength tests for the bench press, pull over, and the half squat. The upper limb bench press and pull-over tests along with the lower limb back half squat were performed using a 1-repetition maximum protocol. Based on the intraclass correlation coefficient and excluding the agility T-test (ICC = 0.72), we found excellent relative reliability for all variables (intraclass correlation coefficient range: 0.85-0.96, SEM range: 0.03-3.00). For absolute reliability or coefficients of variation, 71% (5/7) of the variables were excellent (CV < 5%). The circuit strength training group showed significant interaction effects and relevant effect sizes for the 12-week training period (8/9, 89%), and the mean effect size for the CT was markedly higher (d = 1.3, range: 0.41 - 2.76) than in the CG (d = -1.0, range: -0.73 - 0.29). The largest improvements were in the Yo-Yo test (d = 2.76) and the squat jump (d = 2.05). These results show that a 12-week circuit strength training program is an effective method to increase handball-related performance characteristics.